Assessing the effect of mandatory progress reporting on treatment requirements identified during health examinations at the Fukushima Daiichi Nuclear Power Plant: A time series analysis. Issue 1 (22nd January 2020) - Mori, Koji; Tateishi, Seiichiro; Kubo, Tatsuhiko; Kobayashi, Yuichi; Hiraoka, Ko; Kawashita, Futoshi; Hayashi, Takeshi; Kiyomoto, Yoshifumi; Kobashi, Masaki; Fukai, Kota; Tahara, Hiroyuki; Okazaki, Ryuji; et al.
Abstract: Objectives: At the Fukushima Daiichi Nuclear Power Plant, run by the Tokyo Electric Power Company, new procedures were introduced as part of the fitness for duty program in July 2016. These were designed to ensure that treatment and further investigations identified as necessary during health examinations were carried out. This study aimed to assess the effectiveness of the initiative by testing whether workers who needed further health examinations obtained them promptly, and whether the number with unmet health needs decreased and the number of workers being treated increased. Methods: The primary contractors reported aggregated quarterly results of health examinations of both their own and their subcontractors' employees, and follow‐up visits to medical institutions were also reported over the next two quarters. The study used data for the period from July 2016 to December 2018. Incident rate ratios were estimated using a multilevel Poisson regression model, including the logarithm of the number of workers who took health examination for each primary contractor company as offset. The linear trend was assessed by treating the number of periods as a continuous variable. Results: The incident rate ratio for workers who needed treatment having a follow‐up examination promptly showed a significant decrease over time. The incident rate ratio for those with unmet needs decreased, and those being treated increased over time. Conclusions: The findings showed that the initiative was effective, with the number of early visits for further health examinations increasing and a decrease in the number of people with unmet health needs.